Translating research into action: Policy recommendations for strengthening antiretroviral therapy adherence in Ghana based on empirical evidence - Victor Luckyboy Dzramado; Obed U. Lasim; Emmanuel Oduro (PLoS ONE, 2026)
Despite significant advances in antiretroviral therapy (ART) accessibility in Ghana, suboptimal adherence remains a critical challenge undermining treatment effectiveness. This article presents evidence-based policy hypotheses derived from a comprehensive mixed-methods investigation of ART adherence determinants among 2,000 people living with HIV in Ghana#39;s Ashanti Region. We hypothesize that multisectoral policy interventions addressing economic barriers, healthcare system deficiencies, and socio-cultural obstacles will significantly improve adherence rates beyond conventional clinical approaches. Specifically, we propose that: (1) integrated transportation support systems will substantially reduce missed appointments; (2) decentralized medication distribution networks incorporating community-based refill options will improve medication access; (3) restructured clinic operations emphasizing reduced waiting times and privacy protection will enhance engagement; and (4) formalized income protection and nutritional support policies will address critical economic barriers to consistent treatment. These policy hypotheses extend beyond individual-focused interventions to address structural determinants of adherence, offering testable frameworks for evidence-based policy development in resource-limited settings.